New Insights Into the Role of Autoreactive CD8 T Cells and Cytokines in Human Type 1 Diabetes - Bender, Christine; Rajendran, Sakthi; von Herrath, Matthias G. (Frontiers in Endocrinology, 2021)
Since the establishment of the network for pancreatic organ donors with diabetes (nPOD), we have gained unprecedented insight into the pathology of human type 1 diabetes. Many of the pre-existing ‘dogmas,’ mostly derived from studies of animal models and sometimes limited human samples, have to be revised now. For example, we have learned that autoreactive CD8 T cells are present even in healthy individuals within the exocrine pancreas. Furthermore, their ‘attraction’ to islets probably relies on beta-cell intrinsic events, such as the over-expression of MHC class I and resulting presentation of autoantigens such as (prepro)insulin. In addition, we are discovering other signs of beta-cell dysfunction, possibly at least in part due to stress, such as the over-expression of certain cytokines. This review summarizes the latest developments focusing on cytokines and autoreactive CD8 T cells in human type 1 diabetes pathogenesis.